Compensation Management and Employee Motivation of Kunming Haitian Hotel - Zhang Lu; Prapatsorn Kittimanorom (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2019)
The objective of this study was to investigate the compensation management, to study employees' motivation of Kunming Haitian Hotel, and to study the relationship of the compensation management and employees' motivation of the Kunming Haitian Hotel. The research instrument was the questionnaire. Data collected were analyzed through frequency, percentage, mean, standard deviation and Pearson’s correlation coefficient. The sampling of this study was 80 individuals, those gender of female, aged between 26-35 years, graduated with high school, duration of employee 1-5 years, monthly income 3,001-4,500 Yuan. The analytic results of the compensation management and employee motivation of Kunming Haitian Hotel, with mean score of 3.65 was at agreeing to lowest mean scores as follows, the overall was found that the respondents gave importance to level of compensation management was at agreeing, rank first leasers was strategic compensation model, broadband pay model, the comprehensive compensation model was at agree, respectively. In terms of employee motivation, overall the respondents were at agreeing, with a mean score of 3.66. The factors were ranked from highest to lowest mean scores as follows: power, achievement, and affiliation at low level respectively. The results of hypothesis testing showed that the compensation management and employee motivation of the Kunming Haitian Hotel was a strong positive. The statistic significant was .05